Sejarah penglibatan orang Sikh dalam Pasukan Constabulari Bersenjata Borneo Utara, 1882-1949 dan kesan terhadap identiti - Sarjit S. Gill (Penerbit UKM, 2007)
Majority of the Sikhs who migrated to Malaya and North Borneo (Sabah) were involved in security services as police, army and even security guard. This article discusses the history of the Sikhs in the armed forces since Syarikat Berpiagam Borneo Utara British established the Armed Constabulary in North Borneo in 1882. Their role is significant to saveguard the British colonial interest in the region. It has remained unclear until recently why the British had selected this Sikhs and not other ethnic groups as part of the armed forces. The article highlights that British trusted the Sikhs as they were viewed as the martial race in British Empire in India, Canada, Fiji, Burma, Hong Kong, New Zealand and Australia. The remaining part of the article then discusses the contribution of the Sikhs to the security forces in North Borneo